Parasite–gut microbiota associations in wild wood mice (Apodemus sylvaticus) - Marsh, Kirsty J.; Raulo, Aura R.; Webster, Joanne P.; Knowles, Sarah C. L. (Frontiers in Microbiology, 2024)
The mammalian gastrointestinal tract provides a habitat for multiple commensal and pathogenic organisms spanning all three domains of life. Both positive and negative interactions occur between gut inhabitants, with potential consequences for host health. Studies of parasite–microbiota associations in natural systems remain scarce, yet are important for understanding how parasite communities and commensal microbiota shape each other, and how these interactions influence host health. Here, we characterize associations between helminth and coccidial infections and gut microbiota profiles in a wild population of wood mice (Apodemus sylvaticus) over 3 years, using two complementary approaches. We first examined parasite–microbiota associations along the length of the gastrointestinal tract through destructive sampling. Then, in a larger non-invasive capture mark-recapture study, we assessed whether gut parasitic infections detected in feces predicted fecal microbiota diversity and composition. We found that while overall microbiota composition was not associated with infection by any common gut parasite species, microbiota richness was associated with gut parasitism in two ways: (i) infection by the trematode Corrigia vitta in the small intestine predicted higher microbiota diversity in the caecum; (ii) there was a negative relationship between gut parasite richness and fecal microbiota richness in the non-invasive study. As our results identified associations between gastrointestinal parasites and microbiota alpha diversity, a future experimental study in this tractable wild mammalian system would be valuable to definitively test the directionality of these interactions.